THE EFFECT OF WASH THE WOUND WITH NORMAL SALINE ON DECREASE THE SURGICAL SITE INFECTIONS POST-APPENDECTOMY (COMPARATIVE STUDY) - Majeed, Zaid Ali; Atya, AliFthala; Naeif, Dr. HaiderYihya (International Journal of Psychosocial Rehabilitation, 2020)
In this study we take (200) case of acute appendicitis who presented to the emergency department of AL- HUSSAIN TEACHING HOSPITAL in period between January 2020 till july 2021 all of them diagnosed as acute appendicitis by clinical ALVARADO score , laboratory tests , ultrasound and C.T. scan . the age of patients in average between 15 to 50 years old , (140) was male and (60) were female . surgery done for all of them , perforated appendix found in (30) patients while (170) patients was not perforated acute appendicitis .( table 2) the follow up of the wound continue for 1 month postoperatively depending on clinical observations for wound and vital signs .